2018
DOI: 10.14297/jpaap.v6i1.294
|View full text |Cite
|
Sign up to set email alerts
|

Term-time Employment and Student Attainment in Higher Education

Abstract: The number of UK full-time university students engaging in term-time employment (TTE) is rising. Students engaging in TTE have previously been found to achieve less well academically than those who do not. This study aimed to explore patterns of TTE and academic achievement of undergraduates at a large UK higher education institution. Self-reported TTE hours were matched to attainment data for 1304 undergraduate students in levels 1-4 of study (SQCF levels 7-10). The majority of students in TTE (71%, n=621) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
5
0
3
Order By: Relevance
“…2018). The study found that one-third of the students work parttime, and another 14% work full-time, during study breaks or term time or both (Dennis et al 2018). Research has shown that the motivations for students to volunteer are twofold, compassion and concern for others, as well as perceived enhanced employability for themselves (Williams et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2018). The study found that one-third of the students work parttime, and another 14% work full-time, during study breaks or term time or both (Dennis et al 2018). Research has shown that the motivations for students to volunteer are twofold, compassion and concern for others, as well as perceived enhanced employability for themselves (Williams et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 survey by Endsleigh Insurance in collaboration with the National Union of Students Insight Team found that 77% of students reported working to help fund their studies, increasing from 59% in 2014 and 57% in 2013. This is not the place for a discussion of the impact of employment on student achievement (see, e.g., Callender, 2008, or Dennis, Lemon, & Louca, 2018), rather, we raise the issue because as French and Kennedy (2017) have noted, the proliferation of competing demands is a key cause of poor attendance. If used appropriately, lecture capture has the potential to support not only traditional learners as they transition to an independent mode of learning but a more diverse and flexible higher education landscape.…”
Section: Lecture Capture and Self-regulationmentioning
confidence: 99%
“…Logan et al (2015) found that students who worked more than 20 h a week at off-campus jobs were more likely to have GPAs that were lower than those who worked fewer hours, while Hovdhaugen (2015) found that the risk of dropout increased when students worked more than 20 h a week. On the other hand, Dennis et al (2018) found that students who worked more than 30 h a week have a significantly lower mean end-of-year grade than those who were not undertaking term-time employment.…”
Section: Insights From the Literaturementioning
confidence: 91%
“…The adverse effects of term-time employment on students’ academic achievement had been widely established. Barke et al (2000); Hunt et al (2006); Curtis and Shani (2002); Wenz and Yu (2010); Hovdhaugen (2015) and Dennis et al (2018) were among the few who had found a decline in academic performance and less time for study. Instead of lower academic grade achievement, Grant et al (2005) found that term-time employed students were more likely to have higher dropout rates and took longer to complete their studies.…”
Section: Insights From the Literaturementioning
confidence: 99%
See 1 more Smart Citation